2014
DOI: 10.1093/pcp/pcu149
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a miR393-Resistant Form of Transport Inhibitor Response Protein 1 (mTIR1) Enhances Salt Tolerance by Increased Osmoregulation and Na+ Exclusion in Arabidopsis thaliana

Abstract: Soil salinity is a common environmental stress factor that limits agricultural production worldwide. Plants have evolved different strategies to achieve salt tolerance. miR393 has been identified as closely related to biotic and abiotic stresses, and targets F-box genes that encode auxin receptors. The miR393-TIR1/AFB2/AFB3 regulatory module was discovered to have multiple functions that manipulate the auxin response. This study focused on miR393 and one of its targets, TIR1, and found that they played potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 59 publications
2
55
0
1
Order By: Relevance
“…Previous studies demonstrated that miR393 is involved in plant responses to drought, salt stresses and auxin treatment in annual species (Chen et al ., , ; Gao et al ., ; Xia et al ., ). In this study, we investigated its role in perennial grass species, creeping bentgrass.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies demonstrated that miR393 is involved in plant responses to drought, salt stresses and auxin treatment in annual species (Chen et al ., , ; Gao et al ., ; Xia et al ., ). In this study, we investigated its role in perennial grass species, creeping bentgrass.…”
Section: Resultsmentioning
confidence: 97%
“…Next, we quantitatively analysed miR393 expression in response to salt, drought, and heat stresses and IAA treatment in leaves. Mature miR393 was found to be significantly induced by these abiotic stressors and auxin treatment (Figure S1b–e), in agreement with observations in Arabidopsis and rice (Chen et al ., , ; Gao et al ., ; Xia et al ., ), suggesting that miR393 is also regulated by various abiotic stresses and hormone auxin in creeping bentgrass.…”
Section: Resultsmentioning
confidence: 99%
“…miR393 has been identified as closely related to biotic and abiotic stresses and was found to target TIR1 genes in this work. TIR1 has been shown to have a role in enhancing plant stress tolerance (Chen et al, 2015). The down-regulation of NNU_ghr-miR393, NNU_gma-miR393h, and NNU_ata-miR393-5p resulted in increased expression level of TIR1 genes.…”
Section: Resultsmentioning
confidence: 99%
“…Downregulation of OsTIR1 and OsAFB2 via OsmiR393 led to reduced tolerance to salt and drought in rice [40]. In contrast, overexpression of a miR393-resistant form of mTIR1 enhanced salt tolerance in Arabidopsis [41]. However, less is known about the role of the miR393/TIR1 homolog module in the stages of fruit development.…”
Section: Discussionmentioning
confidence: 99%